Mixed Halide Isothiocyanate Tin(II) Compounds, SnHal(NCS): Signs of Tetrel Bonds as Bifurcated Extensions of Long-Range Asymmetric 3c-4e Bonds - Hans Reuter (Molecules)
As part of a systematic study on the structures of the mixed halide isothiocyanates, SnIIHal(NCS), their single crystals were grown and structurally characterized. For Hal = F (1), the SnClF structure type was confirmed, while with Hal = Cl (2), Br (3), and I (4), there are three isostructural compounds of a new structure type, and for Hal = Cl (5), there is a second modification of a third structure type. These structure types have been described with respect to the composition and coordination geometry of the first, second, and van der Waals crust coordination spheres and their dependence on the halogen size and thiocyanate binding modes. With respect to the first coordination spheres, all three structure types constitute one-dimensional coordination polymers. In 1, “ladder”-type double chains result from μ3-bridging fluorine atoms, and in 2–4, single-chains built up from μ2-halogen atoms are pairwise “zipper”-like interconnected via κ2NS-bridging NCS ligands, which manage the halogen-linked chain assembly in the double chains of 5. Based on the octet rule, short atom distances are interpreted in terms of 2c-2e and various (symmetrical, quasi-symmetrical, and asymmetrical) kinds of 3c-4e bonds. Weak contacts, the topology of which suggests the extension of the latter bonding concept, are identified as electron-deficient, bifurcated tetrel bonds.